Peran PKBI Kota Semarang dalam Meningkatkan Awareness Kesehatan Reproduksi dan Seksual pada Waria - Sari, Nafa Diana; Rochmawati, Nikmah; Mudzkiyyah, Lainatul (Jurnal Konseling dan Psikologi Indonesia, 2025)
This study aims to explore the role of PKBI Semarang City in increasing awareness of reproductive and sexual health in the transgender community. The study used a qualitative approach with a phenomenological method, through in-depth interviews with two PKBI field officers and two beneficiaries (transvestites). The results of the study showed that the community-based approach carried out by PKBI, such as implementing education through community forums, mobile VCT services, distributing condoms and lubricants, and providing PrEP, succeeded in building trust and increasing awareness of transgender people regarding the importance of maintaining sexual health. Beneficiaries showed positive behavioral changes such as the use of protective equipment, participation in HIV testing, and increased understanding of sexual health. However, challenges in the form of social stigma and discrimination are still significant obstacles. This study emphasizes the importance of a participatory and inclusive approach in sexual health interventions for marginalized groups and encourages the need for public education to create a more supportive social environment.